Neurobiology of Insomnia - Bernd Feige; Raphael J. Dressle; Dieter Riemann (Current Sleep Medicine Reports, 2026)
Abstract Purpose of review In this review about the neurobiology of insomnia, we summarize the currently known areas of neurobiological differences in insomnia structured by polysomnography, stress system, electroencephalography, neuroimaging and genetics. In each chapter we note early seminal work, recent additions and current meta-analytical work, thereby synthesizing available knowledge. Recent findings While heritability of insomnia is significant, many genes are involved. Similarly, in brain morphology no single region stands out. The most common findings across modalities of investigation relate to hyperarousal as well as emotional dysregulation. The considerable pathophysiological heterogeneity in insomnia may still be assessed by neurophysiological methods and used to inform therapeutic approaches. Summary Despite promising methodological advances, group studies converge on relatively unspecific terms such as hyperarousal, and detailed pathophysiological mechanisms are underreported. The investigation of better differentiated subgroups and of intraindividual changes, e.g. therapy effects, should yield more insight in the future.